Influential Publications and Bibliometric Approach to Heavy Metal Removals for Water - Bashan, Veysi; Cetinkaya, Afsin Y. (SPRINGER INT PUBL AG, 2022)
Heavy metals are elements that can have toxic effects even at low concentrations. Heavy metal pollution is one of the most concerning issues at the global level because of the health risks it causes and its negative effects on the ecosystem. Many studies have been carried out in the past years to reduce heavy metal emissions, pollution, and their effects on health. In this context, a scientometric study was conducted to show how this topic has developed academically and to identify effective studies in the field of heavy metal removals for water. When the Web of Science (WoS) database is searched, a total of 22,911 articles were collected based on the heavy metal removals for water subjects, and then, articles were sorted and the top 100 most cited articles were determined. By determining the top 100 most cited articles on this subject, bibliometric analysis has been carried out by covering co-occurrence, co-citation analysis, cluster analysis, and much more. When these top 100 most cited articles were examined, it was seen that review articles were in the majority (59%), and there were more studies in environmental sciences, engineering environmental, engineering chemical, biotechnology applied microbiology categories. It has been observed that most of these most cited articles were published between 2007 and 2012, and the citations given to these 100 articles increased almost linearly since 2007. In addition, it has been determined that China ranks first in this regard with 23 articles and 21,137 citations. The working network between countries, institutes/universities has been revealed. It was determined that the words adsorption, heavy metals, and waste were used the most among the keywords. This study is expected to lay the groundwork for future discussions on the subject. Our analysis provides information on technology and informs decision-makers and researchers about the value of new and existing technologies and future opportunities.
Keywords: Bibliometric analysis; Heavy metal; Removal; Water; Treatment; TRENDS; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources